The Role of Teachers in Implementing Multicultural Education in Social Sciences Learning in Elementary Schools - L, Zulkhairiah Azahra; Difla, Fadhilatul; Azizah, Nurul; Irawan, Syahlila Nasywa; Amelia, Alya; Yusnaldi, Eka (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
Considering the complexity of today's global society and the diversity of Indonesian culture, multicultural education is an important concept. The aim of this study was to investigate how elementary school teachers can incorporate multicultural education into social studies teaching. This research uses a subjective methodology with an emphasis on writing concentration that combines philosophical and instructive inquiry. Theories, previous research findings, and educational reports were used as secondary data sources. Multicultural education practices and the role of teachers in selecting inclusive teaching materials, teaching tolerance, utilizing active learning approaches, developing cultural awareness, and community involvement are described using descriptive analysis. These findings suggest that educators play a strategic role in creating learning environments that encourage cultural diversity and inclusion. This exploration adds to strengthening the implementation of multicultural education in Indonesia, and provides an illustration of how educators can play an important role in preparing students to live in a multicultural and global society.